(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. This study was aimed to evaluate the correlation of body mass index (BMI), waist circumference (WC), and waist-stature ratio (WSR) with urinary composition in urolithiasis patients. Materials and Methods. Medical reports of 1410 urolithiasis patients referred to a tertiary in Tehran, from 2010 to 2015, were reviewed. Collected data included WC, BMI, and WSR, 24-hour urine composition, and the first-morning urine pH. Urinary relative supersaturation of calcium oxalate, calcium phosphate, and uric acid were calculated. Linear correlation and logistic regression models were used for study analyses. Results. A total of 511 records were reviewed. In the women, supersaturation of calcium oxalate significantly correlated with BMI, WC, and WSR. Supersaturation of uric acid significantly correlated with WC. Using regression analyses, BMI and WSR were associated with greater supersaturation of calcium oxalate abnormality, which persisted after adjustment for confounding factors (odds ratio, 1.080; 95% confidence interval, 1.001 to 1.166 for BMI; odds ratio, 1.053; 95% confidence interval, 1.001 to 1.108 for WSR). Larger WC accompanied abnormal values for supersaturation of calcium oxalate; however, the model was marginally significant (odds ratio, 1.032; 95% confidence interval, 1.000 to 1.065; P = .05) in multivariable analysis. In the men on the other hand, none of the obesity indexes were associated with the supersaturation measures. Conclusions. Although both obesity and abdominal obesity correlated with supersaturation of calcium oxalate, mostly by changes in urine volume and pH in women, none of those indexes showed significant correlation with urine composition in the men population of our study.